Being a Kind Leader: Actualization of Kind Leadership in Sirah Nabawiyyah Learning - Fattah, Habib Al; Djono, D; Pelu, Musa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
Kindness in leadership creates many benefits in contemporary organization. It creates healthy relationships, increases organizational effectiveness, and minimizes destructive leadership issue. Considering the positive impact of kind leadership, this article tries to actualize the values of kind leadership in the modern era which are reflected in the discipline of Sirah Nabawiyyah. This was done since Sirah Nabawiyyah is an important part of character education in Islam and it is mandatory to always update it with contemporary issues. This article used literary study as the main method of research. Researcher collected data from credible journals and books related to kind leadership and Sirah Nabawiyyah and then analyzed the data. The results of data collection and analysis showed that there are six capacities that must be acquired to build kind leadership. The six capacities are compassion, integrity, gratitude, authenticity, humility, and humor. These six capacities are portrayed in the leadership pattern of Prophet Muhammad, both in classical and contemporary Sirah Nabawiyyah studies. The analysis of Prophet Muhammad’s leadership also showed that each capacity is connected and supported on one another. The article’s findings are expected to be able to support further studies, especially on kind leadership study which is still unpopular. The findings are also expected to strengthen studies related to historical education-based character education. This study is also expected to be able to continuously update the issues discussed in Sirah Nabawiyyah learning.